Communication Process with Online System between Teachers and Students during the Covid-19 Pandemic at The Primbana Elementary School Medan - Sembiring, Rizki Fitriany Br; Lubis, Lusiana Andriani; Mazdalifah, Mazdalifah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research aims to analyze the communication process between teachers and students, what obstacles are faced by teachers and students and the effort made by teachers to overcome obstacles in carrying out teaching and learning activities during the Covid-19 pandemic at Primbana Elementary School Medan. This research uses constructivism paradigm with descriptive qualitative method. The main informants in the research are teachers and students, while the triangulation as the validity of the data consists of parents and the school committee board. The data analysis technique uses the Miles Huberman model, namely reduction, data presentation and conclusion drawing. The results show that the teacher and student communication process that is carried out in the online system was manifested into four elements, namely the teachers as communicator convey messages to the students in the form of instructions for filling attendances at the beginning of meeting, delivering material and opening discussion session as well as giving daily assignments through various online learning applications such as Google Classroom, Zoom and WhatsApp Group which result in the effect of students being active and not participating in the online learning process. The barriers experienced by teachers and students are technical barriers in in the form of signal disturbances and economic limitations of students’ families to buy data packages, pay tuition and do not have gadgets, communication barriers namely students’ misunderstanding in understanding messages, lack of students understanding of the materials and not conducive learning atmosphere and psychological barriers are disturbances caused by pressures from within students such as shyness in asking questions, not concentrating and being disciplined and taking lessons for granted. The efforts made by the teacher in overcoming these obstacles by evaluating and paying attention to the situation and learning environment  in the form of giving daily assignments as an exercise, taking a long time in collecting assignments, giving praise such as applause and additional activity points as a form of appreciation and teaching how to respect others and implementing two learning systems, namely online and offline to optimize teaching and learning activities in the era of the Covid-19 pandemic.